A Comparative Analysis of Medical and Islamic Sharia Perspectives on Underage Pregnancy - Andriana, Kusuma; Putri Ayuningtyas, Aulia; Siti Nurzulia, Isnaini (Family Medicine Department, Faculty of Medicine, Brawijaya University, 2025)
Pregnancy among females under 19 is a global health crisis impacting adolescents' biological, psychological, social, and spiritual well-being. It carries high risks of medical complications, such as anemia and preterm birth, alongside considerable emotional and social stress. Within Muslim societies, this issue also involves moral and Islamic legal dimensions, highlighting the necessity of preserving personal dignity and ensuring legitimate lineage. This systematic review, following PRISMA 2020 guidelines, collected literature from 2020–2025 using keywords